2002
DOI: 10.1073/pnas.252340199
|View full text |Cite
|
Sign up to set email alerts
|

De novo designed peptide-based amyloid fibrils

Abstract: Identification of therapeutic strategies to prevent or cure diseases associated with amyloid fibril deposition in tissue (Alzheimer's disease, spongiform encephalopathies, etc.) requires a rational understanding of the driving forces involved in the formation of these organized assemblies rich in ␤-sheet structure. To this end, we used a computer-designed algorithm to search for hexapeptide sequences with a high propensity to form homopolymeric ␤-sheets. Sequences predicted to be highly favorable on this basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
294
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 371 publications
(318 citation statements)
references
References 30 publications
(47 reference statements)
19
294
1
2
Order By: Relevance
“…The system was enclosed by a reflecting sphere of diameter 90 Å (this corresponds to a concentration of 8.7 mM, which is only an order of magnitude larger than the highest concentration used in ref. 26) (Fig. 1a; see also Supporting Text).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The system was enclosed by a reflecting sphere of diameter 90 Å (this corresponds to a concentration of 8.7 mM, which is only an order of magnitude larger than the highest concentration used in ref. 26) (Fig. 1a; see also Supporting Text).…”
Section: Methodsmentioning
confidence: 96%
“…The other peptides are designed sequences used in the study of fibril formation and peptide self-assembly. A␤ 7 , K I , and KFE8 form antiparallel ␤-sheet structures (26)(27)(28), whereas K L forms ␤-sheet aggregates but not fibrils (26). Several peptides were studied to determine sequence-independent characteristics of the dimerization process, because, as already mentioned, many different proteins and peptides can form amyloid fibrils (23,29).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By examining seven other similar sequences Serrano et al were able to show that peptides with a net charge of ±1 had a marked preference for fibril formation over their electrically neutral counterparts. 18 We performed simulations on the STVIYE system with both protonated and deprotonated glutamate to explore the molecular basis for this trend. Simulations were performed using replica exchange molecular dynamics (REMD) with the all-atom CHARMM force field 19 and a generalized Born (GB) implicit solvent model.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results suggest that, probably, α-helix 2 plays an important role in the formation of the amyloid fibril. In this respect, it is interesting to point out that the recent study by Dobson and coworkers [22] has shown that only two small regions in a large protein affect the formation of amyloid fibrils and that designed short hexapeptides can form amyloid fibrils, which cannot be distinguished from the ones made by large proteins [25].…”
Section: Correlation Between Aggregation Propensity and Polypeptide Cmentioning
confidence: 99%